A new model for Last-Mile Delivery and Satellite Depots management: The impact of the on-demand economy. (January 2021) - Perboli, Guido; Brotcorne, Luce; Bruni, Maria Elena; Rosano, Mariangela
Highlights: Introduce a new policy for managing the deliveries - inside the urban areas. Model the policy by means of a new multi-periodic variant of Bin Packing. Develop a MIP model and an accurate heuristic for tackling large-sized instances. Use our model to draw practical insights on the effect of the on-demand economy. Abstract: Two-tier city logistics systems are playing a very important role nowadays in the management of urban freight activities. Although several city authorities have promoted different measures to foster the implementation of small urban consolidation centers in a two-tier system, only a few authors have addressed the joint problem of operating these facilities and providing services to customers. We show how the problem can be modeled as a new variant of the bin packing, for which we provide a mixed integer programming formulation and two heuristics that are shown to be quite effective in solving efficiently and to near optimality the problem. The application of our approach on real data from the city of Turin puts into highlight the superiority of the consolidation approach, including the bundle of goods from different providers, stockholding and other value-added logistics services, over the classical single-tier approach. In addition, the paper provides a thorough analysis of some emerging aspects of the on-demand economy, as the consideration of customers' preferences and the integration of multiple delivery options. The managerial insights coming from this work will be part of the new Logistics and Mobility Plan to be activated in 2022 in the Piedmont region.